The Fall of Interpretation Philosophical Foundations for a Creational Hermeneutic - Smith, James K. A. (Grand Rapids, Michigan Baker Academic, 2012)
James K.A. Smith offers an innovative approach to hermeneutics. The second edition provides updated interaction with contemporary hermeneutical discussions and responds to criticisms. --from publisher description.
Keywords: Hermeneutics -- Religious aspects -- Christianity. Philosophical theology. Fall of man